Didactical Design Principles to Apply When Introducing Student-generated Digital Multimodal Representations in the Science Classroom - Mette Fredslund Andersen; Nicolai Munksby (Stockholm University Press, 2018)
This project studies designs for learning in the multimodal science classroom in primary and lower-secondary schools in Denmark. The aim of the study is to work with teachers to develop a start-up didactic design that raises student awareness of the affordances provided by different representational modes and thus enhances student production of digital multimodal representations as an expression of learning and science culture. The project takes a design-based research (DBR) approach and uses a social-semiotic theoretical framework. Research in using representations for teaching and learning in science reveals that students' potential for learning concepts can be strengthened through the transformation of representations and the production of multimodal representations. The first design principle is to organize activities and dialogues among the students that will enhance awareness of the affordances provided by the different modes of representations. The second design principle is that students, through their own thorough practical experiments and dialogues, learn to use representations that show data. The third design principle is that students produce digital multimodal representations as expressions of their learning and reflect on and evaluate these on the basis of known assessment criteria for multimodal representations in science.